2005
DOI: 10.1002/jhet.5570420215
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 4- and 5- phenyl substituted isoxazoles

Abstract: 5-Phenylisoxazole (4) and 4-phenylisoxazole (22) underwent phototransposition to 5-phenyloxazole (5) and 4-phenyloxazole (24) respectively. Labeling with deuterium or methyl confirmed that these phototranspositions occurred via the P 4 pathway which involves only interchange of the N2 and C3 ring position. Thus, 4-deuterio-5-phenylisoxazole (4-4d), 4-methyl-5-phenylisoxazole (10), and 5-methyl-4-phenylisoxazole (23) phototransposed to 4-deuterio-5-phenyloxazole (5-4d), 4-methyl-5-phenyloxazole (11), and 5-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…In a computational study, it has been shown that bicyclic intermediates are involved (compare 6–8 in Scheme ) . More generally in such reactions, a competition between this mechanism and mechanisms involving homolytic or heterolytic fragmentation of the bond between the two heteroatoms is discussed …”
Section: Photochemical Heteroatom Isomerization Of Heterocyclic Compomentioning
confidence: 99%
“…In a computational study, it has been shown that bicyclic intermediates are involved (compare 6–8 in Scheme ) . More generally in such reactions, a competition between this mechanism and mechanisms involving homolytic or heterolytic fragmentation of the bond between the two heteroatoms is discussed …”
Section: Photochemical Heteroatom Isomerization Of Heterocyclic Compomentioning
confidence: 99%
“…23,24 istražuje izomerizacije izoksazola i benzizoksazola pomoću CASSCF i MP2-CAS računskih metoda. Stariji mehanizam 22,25,26 za te reakcije bio mehanizam je ciklizacije-izomerizacije (shema 3) koji uključuje prvotno nastajanje bicikličkog međuprodukta nakon kojeg slijedi [1,3]-pomak dušika u sekundarni biciklički međuprodukt koji podliježe otvaranju azirinskog prstena u produkte fototranspozicije (P 1 -P 3 ). Ti međuprodukti nisu nikad zamijećeni, te je autor predložio drugi, izravni mehanizam preko stožastog presjeka (CI).…”
Section: Pavlik I Surunclassified
“…Representative examples include: (i) the synthesis of 2-trifluoromethyloxazole 77 from a preparative-scale irradiation at 254 nm in acetonitrile of the easily accessible 3-trifluoromethylisoxazole 76 [51]; and The isoxazole-to-oxazole rearrangement has been also used in the synthesis of benzocondensed derivatives. The irradiation of benzisoxazoles 81 in water (highpressure Hg lamp) produces almost quantitative yields of the corresponding benzoxazoles 82 (Scheme 12.24) [53].…”
Section: Oxazolesmentioning
confidence: 99%